Mitochondrial DNA differentiates Alzheimer's disease from Creutzfeldt‐Jakob disease. Issue 5 (21st January 2016) - Podlesniy, Petar; Llorens, Franc; Golanska, Ewa; Sikorska, Beata; Liberski, Pawel; Zerr, Inga; Trullas, Ramon
Abstract: Introduction: Low content of cell‐free mitochondrial DNA (mtDNA) in cerebrospinal fluid (CSF) is a biomarker of early stage Alzheimer's disease (AD), but whether mtDNA is altered in a rapid neurodegenerative dementia such as Creutzfeldt‐Jakob disease is unknown. Methods: CSF mtDNA was measured using digital polymerase chain reaction (dPCR) in two independent cohorts comprising a total of 112 patients diagnosed with sporadic Creutzfeldt‐Jakob disease (sCJD), probable AD, or non‐Alzheimer's type dementia. Results: Patients with AD exhibit low mtDNA content in CSF compared with patients diagnosed with sCJD or with non‐Alzheimer's type dementias. The CSF concentration of mtDNA does not correlate with Aβ, t‐tau, p‐tau, and 14‐3‐3 protein levels in CSF. Discussion: Low‐CSF mtDNA is not a consequence of brain damage and allows the differential diagnosis of AD from sCJD and other dementias. These results support the hypothesis that mtDNA in CSF is a pathophysiological biomarker of AD.